Acetabular Component Orientation in Total Hip Arthroplasty: The Impact of Obesity. Issue 3 (May 2014) - McArthur, Benjamin A.; Vulcano, Ettore; Cross, Michael; Nguyen, Joseph; Della Valle, Alejandro G.; Salvati, Eduardo
Introduction: Acetabular component position can be an important determinant of joint stability and bearing surface wear after THA. Nonetheless, the incidence of malpositioning is high. Patient obesity, low surgeon volume, and minimally invasive approaches are known risk factors for malposition. As the incidence of obesity continues to increase, it is important to recognise its effect on intraoperative component positioning in THA. Objectives: Our goal was to assess the impact of obesity on component position for a high-volume surgeon using a standard postero-lateral approach. Methods: A consecutive series of 120 obese (BMI >30, mean BMI 34.4) and 120 non-obese patients (mean BMI 25.4), who had undergone primary THA by a single surgeon, were included in our retrospective study. AP pelvis and cross-table radiographs obtained at the first postoperative visit were analysed using EBRA software to determine inclination and anteversion angles. Optimal position was defined as 30-45° of inclination and 5-25° of anteversion. Results: Mean inclination and anteversion were 40.6 (+/-5.4°) and 16.6 (+/-5.5°) respectively, in the obese group and 39° (+/-5.0°) and 16.2° (+/-7.5°) in the non-obese group. In the obese group 89 (74%) patients were within the desired range for both measurements, 31 (26%) were out of range in at least one, compared to 91 (76%) and 29 (24%) in the non-obese group, respectively. The overall incidence of malpositioning was 25% for both groups. Among outliers, mean deviation from the optimal range was ≤3.8° in both groups. Conclusions: The risk of component malpositioning in THA may be reduced when surgery is performed by an experienced, high volume surgeon utilising a standard posterolateral approach. In this setting the deleterious effect of obesity may be overcome.